The role of information and communication technology for development in Brazil. Issue 1 (2nd January 2017) - Malaquias, Rodrigo Fernandes; de Oliveira Malaquias, Fernanda Francielle; Hwang, Yujong
ABSTRACT: Social, human and economic dimensions of development demand relevant attention in developing and developed countries. In this paper, we explore the role of information technology (IT) for development in an emerging economy: Brazil. Through our analysis and discussion, we highlight relevant issues to be considered by information systems (IS) literature. For example, we observed IT advances in the health area, and these advances include telemedicine, applications focused on cancer, applications for prescription process, electrocardiogram in the clouds, and remote tele-monitoring of chronic patients. During the literature review, we also found two initiatives in Brazil that help in the fight against cancer and HIV with IT use. These (and other) measures have a direct effect on social and human development. We indicate a special attention to the importance of government actions and of the internet to leverage the relationship between IT investments and development in emerging economies.